2010
DOI: 10.1243/09544062jmes2199
|View full text |Cite
|
Sign up to set email alerts
|

Designing and testing a hydraulic inerter

Abstract: This article proposes a novel hydraulic inerter and experimentally verifies its properties. The inerter is a true two-terminal mechanical network element, which was invented to substitute for the mass in mechanical/electrical analogies. Previously, inerter concepts have been realized by rack-and-pinion and ball-screw devices. This article introduces a new hydraulic inerter device in which the forces are translated by hydraulic means. The dynamics of the device is discussed and experimentally verified. On the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(99 citation statements)
references
References 10 publications
0
95
0
Order By: Relevance
“…The constant of proportionality is termed “inertance” and is measured in mass units (kg). Notably, several different inerter prototypes were devised and experimentally tested over the past decade achieving inertance values orders of magnitude larger than the devices' physical mass, while observing a linear behavior within relatively wide frequency bands of practical interest . These devices are relatively small‐scale tailored for and used in vehicle suspension systems.…”
Section: Introductionmentioning
confidence: 99%
“…The constant of proportionality is termed “inertance” and is measured in mass units (kg). Notably, several different inerter prototypes were devised and experimentally tested over the past decade achieving inertance values orders of magnitude larger than the devices' physical mass, while observing a linear behavior within relatively wide frequency bands of practical interest . These devices are relatively small‐scale tailored for and used in vehicle suspension systems.…”
Section: Introductionmentioning
confidence: 99%
“…The constant of proportionality of the inerter is called the inertance, which has the dimension of mass. Inertance is typically generated from the rotation of a flywheel, and there are 3 main types of inerter devices: rack and pinion inerter devices, ball and screw inerter devices, and hydraulic inerter devices …”
Section: Introductionmentioning
confidence: 99%
“…An appealing property of inerters is that they can be designed and realized in practice having their inertance significantly larger than their mass [1,2]. This opens many interesting possibilities so that many authors reported on how to design and use inerters to suppress mechanical vibrations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Another type of mechatronic inerter utilizes a rotary DC motor shunted with an appropriate electrical circuit [4]. An inertance-like behaviour can also be accomplished through a scheme in which hydraulic fluid is accelerated [5,6] with a piston which pushes the fluid through a helical channel [6].…”
Section: Introductionmentioning
confidence: 99%